Adopsi Strategi Kreatif dari Kreator Kuliner @BeruangRakus Pada Platform Tiktok - Oentoro, Alicia Cheryl; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The rapid growth of TikTok users shows that audiences are increasingly looking for informative and entertaining content. Culinary content is one of the most popular categories, especially among the younger generation. The @BeruangRakus account is one culinary content account that adopts a creative strategy by creating unique and interesting content. Based on interviews with audiences and experts in the field of digital content, it was found that the use of attractive visuals, strong narratives, and creative editing are very important to attract the audience's attention. Distinctive features in content, consistency, as well as trend analysis and collaboration with influencers were also identified as crucial factors in building identity and increasing engagement. In addition, the authenticity of content is an important aspect to avoid ethical and copyright issues. This research links the relevance of communication theory in understanding the impact of culinary content on consumer decisions and audience engagement, providing valuable insights for content creators and marketers in designing content strategies in the digital era. The results of the study show that the adoption of creative strategies in content creation determines success in the competitive digital era. The adoption of creative strategies demonstrates the importance of keeping up with the latest trends. Pertumbuhan pengguna TikTok yang pesat menunjukkan bahwa audiens semakin mencari konten yang informatif dan menghibur. Konten kuliner menjadi salah satu kategori yang paling diminati, terutama di kalangan generasi muda. Akun @BeruangRakus merupakan salah satu konten kuliner yang mengadopsi strategi kreatif dengan membuat konten unik dan menarik. Berdasarkan wawancara dengan audiens dan ahli di bidang konten digital, ditemukan bahwa penggunaan visual menarik, narasi yang kuat, dan editing kreatif sangat penting untuk menarik perhatian audiens. Ciri khas dalam konten, konsistensi, serta analisis tren dan kolaborasi dengan influencer juga diidentifikasi sebagai faktor krusial dalam membangun identitas dan meningkatkan keterlibatan. Selain itu, keaslian konten menjadi aspek penting untuk menghindari isu etik dan hak cipta. Penelitian ini mengaitkan relevansi teori komunikasi dalam memahami dampak konten kuliner terhadap keputusan konsumen dan keterlibatan audiens, memberikan wawasan berharga bagi creator konten dan pemasar dalam merancang strategi konten di era digital. Hasil penelitian menunjukkan bahwa adopsi strategi kreatif dalam pembuatan konten menentukan keberhasilan di era digital yang kompetitif. Adopsi strategi kreatif menunjukkan pentingnya mengikuti tren terkini.